Is Storytelling Marketing Effective in Building Customer Engagement and Driving Purchase Decisions? - Mavilinda, Hera Febria; Putri, Yulia Hamdaini; Nazaruddin, Akhmad (Universitas Muhammadiyah Yogyakarta, 2023)
Research aims: This study examines the relationship between storytelling marketing and customer engagement and its direct and indirect influence on purchasing decisions. Customer engagement serves as an intervening variable mediating the relationship between storytelling marketing and purchasing decisions.Design/Methodology/Approach: The research questionnaire was distributed to 200 respondents over 17 years who were active users of Instagram social media. The data analysis technique was a quantitative method employing Analysis of Structural Equation Modelling (SEM) operated through the Analysis of Moment Structure (AMOS) program.Research findings: The study's results demonstrated that storytelling marketing directly and significantly affected customer engagement and did not directly affect purchasing decisions. In addition, there was a positive and significant influence between customer engagement and purchasing decisions, and customer engagement mediated the relationship between storytelling marketing and purchasing decisions. Theoretical Contribution/Originality: Research on storytelling marketing in the context of social media platforms is new in marketing. Most previous research discussed the relationship of storytelling marketing to brand reinforcement and identity. Therefore, this study attempted to integrate the relationship model between storytelling marketing and purchasing decisions by adding customer engagement as an intervening variable.Practitioners/Policy Implications: This research can provide marketers insight into creating exciting and creative marketing content through storytelling marketing that can encourage consumer involvement in a brand or product to generate follow-up action and influence consumer purchasing decisions.Research Limitations/Implications: This research only focused on marketing storytelling and customer engagement variables, generally influencing consumer purchasing decisions on the Instagram social media platform. Hence, future research can focus more on one research object from a brand or product and develop other variables related to customer engagement from a different perspective.